Pengaruh Model Pembelajaran Problem Based Learning terhadap Kemampuan Berpikir Kritis Siswa pada Materi Usaha dan Energi: The Influence of the Problem Based Learning Model on Students' Critical Thinking Skills in the Material of Work and Energy - Margareta Ane; Samsul Bahri (ITScience (Information Technology and Science), 2026)
This study aims to determine the effect of the Problem-Based Learning (PBL) learning model on students' critical thinking skills in the work and energy material in class XA of SMA Negeri 1 Entikong. This study uses a quantitative approach with a one-group pretest–posttest design. The research subjects were 15 Class XA students who were purposively selected. The data collection instrument was an essay test consisting of six questions, arranged according to the FRISCO critical thinking indicators: Focus, Reason, Inference, Situation, Clarity, and Overview. Data analysis was carried out through the Shapiro–Wilk normality test and the Paired Sample t-Test test with the help of IBM SPSS software version 26. The results showed that the average pretest score of 54.86 increased to 80.46 in the posttest after the PBL learning model was applied. In addition, the scores on each FRISCO indicator were quite good: Focus 11.93; Reason 10.13; Inference 10.33; Situation 12.00; Clarity 12.33; and Overview 9.46. The results of the normality test indicate that the data are normally distributed, with pretest p-value of 0.488 and posttest p-value of 0.061 (both > 0.05). Meanwhile, the results of the Paired Sample t-Test show a significance value (2-tailed) of 0.000, with a calculated t value of -9.381 and a t table of 2.144, indicating a significant difference in students' critical thinking abilities before and after treatment. Thus, the Problem-Based Learning model has been proven effective at significantly improving students' critical thinking skills with respect to the material on work and energy.